PIC based hand-held IC tester - Liew, Choon Siong (2009)
Nowadays, electrical devices are very common in our life, for example televisions, computers, cellular phones, remote control, automobile etc. All the electrical devices consist of integrated circuits (ICs). As the FKEE students, dealing with ICs has become a norm. However, the IC tester used in laboratory to verify the availability of the ICs is big, not portable, heavy and expensive. Thus, a hand-held IC tester is developed to test common ICs used in the laboratory. In this project, the microcontroller used is PIC18F4525 to control the operation of the system. In addition, it is equipped with a numerical keypad, keypad encoder, IC socket, liquid crystal display screen, beeper and a 9V cell battery power supply. The ICs to-be-tested will be placed into IC socket. The code of the IC will be keyed in by using the keypad. Then, the outcome of the test will be shown at the LCD screen and beeper to indicate the status of the ICs. The system is compact, portable and can test various forms of 20 pins ICs such as basic logic gate, multiplexer, de-multiplexer, encoder, decoder, counter, flip-flop, and etc.